Maternal programming of offspring antipredator behavior in a seabird. (23rd January 2018) - Morales, Judith; Lucas, Alberto; Velando, Alberto
Abstract : Mothers can transmit information to offspring via eggs or via placenta to prepare them for the environment they will experience, but evidence on maternal anticipatory effects is still mixed. Using an experimental approach, we found that gull mothers exposed to predators prior to egg laying had chicks with stronger antipredator responses than chicks of control mothers. Our results suggest that mothers may program offspring behavior via eggs. Abstract: Predation risk is an important environmental factor for animal populations, expected to trigger maternal effects to prepare offspring for living in an environment with predators. Yet, evidence of adaptive anticipatory maternal effects in wild animals is still weak. Here, we explored this question in a wild colony of yellow-legged gulls, Larus michahellis . To this aim, prior to laying we exposed mothers to either mink decoys or nonpredator rabbit decoys and explored the antipredator behavior of 118 chicks at the age of 2 days. We found that chicks from second-laid eggs by predator-exposed mothers crouched faster after hearing a playback with adult alarm calls than chicks from second-laid eggs by control mothers. Besides, chicks from third-laid eggs by predator-exposed mothers were lighter than control chicks, but this was not due to differences in egg volume. Our results suggest that predator-exposed mothers modified offspring phenotype via eggs to cope with predators, although only in chicks from second-laid eggs. Maternal transference of corticosterone could underlie chick behavioral plasticity. Results support the role of maternal effects as a form of phenotype programming to forewarn offspring about environmental hazards.